أثر التكنولوجيا الرقمية على مشروعية القرار الإداري الإلكتروني (Comprehensive Journal of Science, 2026)
Digital technology legitimizes electronic administrative decisions by enabling them to meet basic requirements such as identifying the source, maintaining confidentiality, and ensuring electronic timing, thus strengthening their legal value.New challenges threaten its legitimacy, primarily concerning guarantees for the protection of personal data, non-discrimination in access to digital services, and the protection of users' rights, especially those with limited technical expertise. This necessitates the development of sophisticated digital regulatory frameworks based on standards of security, transparency, and equality to achieve a balance between the efficiency of e-government and the guarantee of rights and freedoms.
Keywords: Technology – Digitalization – Legality – Administrative Decision.